RACISM AND XENOPHOBIA-GLOBAL PROBLEMS - Akram Toshtemirov (European Science Publishing, 2024)
This article analyzes the concepts of racism and xenophobia, their essence. Characteristic features of racism are shown and their differences with concepts such as chauvinism and xenophobia are shown. There has also been some reflection on the ideological basis of racism, the negative consequences of racism in the socio-economic life of states. From a historical and philosophical point of view, as well as at the current stage of the development of science, the complexity of racial research is determined. Attempts have been made to draw holistic conclusions about the main aspects of racism and xenophobia by comparing data from different sources. You will also find information about what the worldview of racist and xenophobic people is, their similarities and differences in nature in this article. Two types of racism stand out: classical and modern (neo-fascism). Under classical racism is understood as the ideology of domination and submission, where social inequality is explained by anthropomorphic characteristics. Modern racism is sublimated racism in which biological emphasis shifts to the field of culture and language. Various forms of racism (domestic, intellectual, institutional, etc.), within the framework of which the intersection of classical and sublimated racism is identified. And xenophobia has the most common types, such as racial, religious, territorial, ethnic, domestic, social. There are also very rarely manifested types of xenophobia: eidjism (insulting attitude towards people with age) , gandikapism (discrimination (discrimination) of a person according to their limited physical capabilities). This article highlights with examples how great these two ideological risks lead to human peace, economic prosperity.
Keywords: racism, eidjism, discrimination, anthropology, xenophobia, Islamophobia.